Influence of High‐Pressure/High‐Temperature Extraction on the Recovery of Phenolic Compounds from Barley Grains. Issue 6 (16th August 2015) - Bucić‐Kojić, Ana; Casazza, Alessandro A.; Strelec, Ivica; Paini, Marco; Planinić, Mirela; Perego, Patrizia
Abstract: The influence of extraction temperature (90–180C), solvent concentration (36–90% ethanol) and time (30–90 min) on extractability of phenolic compounds from barley grains and on antiradical power of extracts was examined. RSM was used to design and optimize the processing parameters. Experimental results of total phenolic contents, total flavonoids and antiradical power of barley extracts were in the range from 3.27 to 26.60 mgGAE /gdb, 0.91 to 6.09 mgCE /gdb and 0.33 to 4.05 gDPPH /mLext, respectively. HPLC analysis of extracts showed epigallocatechin gallate to be the predominant phenolic compound, representing up to 93% of all phenolic compounds determined. Based on RSM analysis, temperature was the most significant factor affecting the observed responses ( P  < 0.05) and optimal extraction conditions were achieved at 180C, 36% ethanol and 90 min. Additionally, strong correlation between protein content and phenolic compounds of extracts was observed ( R  = 0.925), indicating the influence of total proteins on possible overestimation of polyphenol content. Practical Applications: Barley is a cereal crop with potential health benefits related to its content of phenolic compounds. Extraction is one of the essential steps in the isolation of bioactive compounds from natural sources and it is well known that it depends on numerous parameters. The search for nonconventional method of extraction that can overcome drawbacks of conventional (solid‐liquid) extraction was the motivation of this research. Thus, the current study employed high‐pressure/high‐temperature stirred reactor for extraction process, and RSM for modeling the possible relationship between different extraction parameters and yield of phenolic compounds extracted from barley as well as their antioxidant activities. The data shown would provide the scientific rationale for better understanding of extraction of bioactive phenolic compounds from barley at high‐pressure/high‐temperature regime and as a contribution to the development of this technique in spite of the high cost of equipment.